Acute parvovirus B19 infection in identical twins unmasking previously unidentified hereditary spherocytosis. (29th July 2014) - Forde, Donall G; Cope, Alison; Stone, Ben
Abstract : Identical Caucasian male twins, previously fit, presented 1 week apart with short histories of fever and lethargy. The twins were febrile at presentation with profound pancytopaenia and evidence of haemolysis. There was no rash or arthralgia. Both required multiple red cell transfusions. The twins had positive IgM serology for Epstein-Barr virus (EBV), cytomegalovirus (CMV) and parvovirus B19. EBV viral capsid antigen and Epstein-Barr nuclear antigen IgGs were also positive however, suggesting past EBV exposure. Parvovirus B19 DNA was detected from peripheral blood PCR; CMV and EBV DNA PCRs were negative. Convalescent serology demonstrated no evolution of the CMV serological response, that is no IgG to CMV developed which implies an initial non-specific polyclonal IgM response. The twins recovered fully over 7 days, the first with a course of prednisolone and the second spontaneously. They were diagnosed with hereditary spherocytosis on convalescent blood films. On further questioning, a family history of hereditary spherocytosis was eventually revealed. The twins' maternal grandmother was known to have the condition asymptomatically. Their mother had prior to this never been tested, but later bloods would reveal a compatible biochemical picture.